Graft fluorinated poly(arylene ether ketone)s containing highly dense sulfonic-acid-functionalized pendants for proton exchange membranes by C–N coupling. (22nd November 2017) - Xie, Yunji; Liu, Bei; Chen, Zheng; Han, Xiaocui; Liu, Baijun; Zhang, Haibo; Pang, Jinhui; Jiang, Zhenhua
Abstract: A series of poly(arylene ether ketone)s (PAEKs) with dense sulfonic-acid-functionalized pendants were successfully synthesized by the Ullmann C–N coupling of a polymer precursor containing pendant iodobenzene rings and 3, 6-ditrityl-9H-carbazole, followed by sulfonation using chlorosulfonic acid. A tough transparent membrane, which exhibited suitable dimensional stability and high proton conductivity, was obtained by casting an N, N -dimethylacetamide polymer solution. DSPAEK-CZ-25 (IEC = 2.03 meq. g −1, where IEC = ion-exchange capacity) exhibited the highest proton conductivity of 177 mS cm −1 at 100 °C; this value is significantly greater than that of Nafion 117. In terms of molecular design, the large difference in polarity between the fluorinated polymer backbone and the concentrated pendant sulfonic acid groups possibly induces good phase-separation morphology, which enhances conductivity and dimensional stability. The obtained membranes exhibited excellent thermal stabilities and good mechanical properties. Overall, the DSPAEK-CZ polymers exhibited outstanding comprehensive performance as potential materials for proton exchange membranes (PEMs). Graphical abstract: Preparation of proton exchange membranes with functional pendants using Ullmann C-N coupling reaction is detailed in this work. Membranes show well-defined phase-separation resulting in sufficient proton conductivity and modest dimensional stability. The membranes exhibited outstanding performance as good candidate proton-exchange membrane materials for fuel cells applications. Highlights: Using Ullmann C-N coupling to synthesize poly(arylene ether ketone)s with dense sulfonic-acid-functionalized pendants. Multiphenyl substituted difluoride monomer is not required in synthesis procedure, avoiding complex synthetic procedures. The large difference in polarity of polymer matrix enables the formation of well-defined nanophase-separated structures. With an IEC value of 1.72 meq.·g −1, the membrane exhibits excellent dimensional stability and high proton conductivity.